Antibacterial Activity and Toxicity Profiles of Eclipta prostrata (L.) L. Extracts and Conventional Antibiotics against Bacterial Triggers of Some Autoimmune Diseases - Cai, Tianchen; Cock, Ian E. (Pharmacognosy Communications)
Background: Eclipta prostrata (L.) L. has been used traditionally to treat numerous diseases, including many caused by bacterial pathogens. However, E. prostrata extracts are yet to be tested for the ability to inhibit the growth of bacterial triggers of autoimmune diseases. Materials and Methods: Antimicrobial activity was assessed using disc diffusion and liquid dilution minimum inhibitory concentration (MIC) assays against a panel of bacterial triggers of some autoimmune diseases. Interactions between the E. prostrata extracts and conventional antibiotics were studied and classified using the sum of the fractional inhibitory concentration (∑FIC). The toxicity of the individual samples and the combinations was assessed using the Artemia lethality assay (ALA). Results: Eclipta prostrata leaf extracts displayed notable antibacterial activity against the bacterial triggers of rheumatoid arthritis (P. mirabilis and P. vulgaris), ankylosing spondylitis (K. pneumoniae), and multiple sclerosis (A. baylyi and P. aeruginosa). The aqueous extract was a particularly good inhibitor of Proteus spp. growth. (MICs = 165μg/mL), whilst lower potency was noted against other bacterial pathogens. Furthermore, combining the extracts with conventional antibiotics resulted in potentiation of the inhibitory activity for some combinations, particularly those containing chloramphenicol as the antibiotic component. None of the individual components (nor the combinations) were toxic in the ALA assay. Conclusion: The E. prostrata methanolic, aqueous and ethyl acetate extracts displayed clinically relevant antibacterial activity against P. mirabilis and P. vulgaris, and lower potency against K. pneumonia, A. baylyi and P. aeruginosa when tested alone. The lack of toxicity of the extract and combinations indicates that E. prostrata extract and antibiotic combinations may provide leads in the development of new therapies to prevent and treat the autoimmune diseases rheumatoid arthritis, ankylosing spondylitis and multiple sclerosis.
Keywords: Bringaraja; Medicinal plants; Rheumatoid arthritis; Ankylosing spondylitis; Multiple sclerosis; Conventional antimicrobials; Synergy; Drug interaction